Records re the Danish West Indies - Danish West Indies
Chiefly records concerning British depredations on commerce of the Danish West Indies during the American Revolution. Also includes an appointment to office (1823 August 12) and memorabilia.
In part, handwritten and typewritten transcripts.
Collection material in Danish, with English and French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States Virgin Islands -- Commerce; United States -- History -- Revolution, 1775-1783 -- Naval operations, British